Black-White Segregation, Discrimination, and Home Ownership - Kelly DeRango (W.E. Upjohn Institute for Employment Research, 2001)
The effect of discrimination on black-white racial segregation is studied using a confidential supplement of the Panel Study of Income Dynamics (PSID). Audit studies reveal that the rate of discrimination in rental housing is substantially higher than in owner-occupied housing. Thus, a variable indicating home ownership is used to proxy for the discrimination rate faced by blacks. The fixed-effects estimates of segregation imply that home ownership is associated with a decline in black-white segregation. This effect decreases slightly at higher income levels but increases substantially with the education of the head of household. Evidence is presented that the effect of discrimination on segregation disappears in cross-sectional data but reappears when using a panel and controlling for fixed-effects. The findings of this study suggest that increased government enforcement of fair housing laws may have a quantitatively different effect on different segments of society and that future research on racial segregation should emphasize the use of panel, as opposed to cross-sectional, data.
Keywords: J7; I3; 330; housing; discrimination; segregation; DeRango